Flexible and Adaptable Restoration: An Example from South Korea. Issue 3 (May 2014) - Temperton, Vicky M.; Higgs, Eric; Choi, Young D.; Allen, Edith; Lamb, David; Lee, Chang‐Seok; Harris, James; Hobbs, Richard J.; Zedler, Joy B.
Abstract Ecological restoration is set to play a key role in mitigating biodiversity loss. While many restorationists worry about what to do about and what to call rapidly changing ecosystems (no‐analog, novel, or other terms), ecologists and managers in some parts of the world have avoided these controversies and proceeded with developing and implementing innovative restoration projects. We discuss examples from South Korea, including the Cheonggyecheon river project in Seoul and the new National Institute of Ecology, which combines scientific research, planted reference systems for future restoration, and an Ecorium for outreach and education. South Korea faces a range of restoration challenges, including managing even‐aged planted forests, major land use changes (especially urbanization) affecting valuable tidal flats, and fragmented landscapes caused by intensive land use and the fenced Demilitarized Zone (DMZ). The examples from South Korea provide insights that might guide future actions more broadly. These include flexible targets for restoration not based on historical precedents, considering ecosystem functions and functional trait diversity as well as species composition, creating model restoration projects, and managing adaptively.